The final storm - Michaels, Fern (Kensington Publishing Corp., 2026)
"In her award-winning wildlife photographs, Charlotte Gray captures all the beauty and wonder of the natural world. Far better to focus on breathtaking landscapes than to turn the lens on her own painful childhood and the uncaring mother she left behind in Florida. Piece by piece, Charlotte has built a new, independent life, one she's eager to protect. A chance encounter on assignment in Las Vegas sparks an intriguing relationship, and for the first time, Charlotte impulsively follows her heart. But along with love and fresh beginnings comes a trove of secrets about her new husband. And someone in his past is determined to upend Charlotte's happiness by threatening what she cares about most. After everything she's weathered, Charlotte is about to face the task of rebuilding her life yet again. But this time she's doing it with hard-won strength, experience, and the wisdom to know when to forgive, when to let go, and how to walk into the sunshine and claim the support and love she deserves..."--Dust jacket flap.